Innovation trends in electrolysers for hydrogen production - Pasimeni, Francesco (European Patent Office : International Renewable Energy Agency, 2022)
Electrolysis of water, using renewable electricity, is the sustainable option to produce green hydrogen as an attractive low-carbon energy carrier. To respond to the growing demand for renewables-based hydrogen, an extraordinary expansion of the market for electrolysers is needed linked to a significant capacity increase in the manufacture and deployment of electrolysers. A rapid reduction in electrolyser system costs is essential and technology innovation is crucial to this end. According to IRENA, investment costs for electrolyser plants can be reduced by 40% in the short term and 80% in the long term through key strategies such as improved electrolyser design and construction, economies of scale, replacing scarce materials with abundant metals, increasing efficiency and flexibility of operations, and learning rates with high technology deployment aligned with a 1.5°C climate target.
Patent insight report.
Keywords: Water -- Electrolysis.; Hydrogen.; elektronické knihy; electronic books